Linking biodiversity, ecosystem services, and human well-being: three challenges for designing research for sustainability - Bennett, E. M. (2015)
Ecosystem services have become a mainstream concept for the expression of values assigned by people to various functions of ecosystems. Even though the introduction of the concept has initiated a vast amount of research, progress in using this knowledge for sustainable resource use remains insufficient. We see a need to broaden the scope of research to answer three key questions that we believe will improve incorporation of ecosystem service research into decision-making for the sustainable use of natural resources to improve human well-being: (i) how are ecosystem services co-produced by social–ecological systems, (ii) who benefits from the provision of ecosystem services, and (iii) what are the best practices for the governance of ecosystem services? Here, we present these key questions, the rationale behind them, and their related scientific challenges in a globally coordinated research programme aimed towards improving sustainable ecosystem management. These questions will frame the activities of ecoSERVICES, formerly a DIVERSITAS project and now a project of Future Earth, in its role as a platform to foster global coordination of multidisciplinary sustainability science through the lens of ecosystem services.